Effectiveness of vortioxetine in patients with major depressive disorder and comorbid Alzheimer’s disease in routine clinical practice: An analysis of a post-marketing surveillance study in South Korea - Cumbo, Eduardo; Adair, Michael; Åstrom, Daniel Oudin; Christensen, Michael Cronquist (Frontiers in Aging Neuroscience, 2023)
Background Vortioxetine has demonstrated procognitive effects in patients with major depressive disorder (MDD). We assessed the effectiveness and safety of vortioxetine in a cohort of patients with MDD and comorbid Alzheimer’s disease participating in a large post-marketing surveillance study in South Korea. Methods Subgroup analysis of a 6-month, prospective, multicenter, non-interventional cohort study in outpatients with MDD with a pre-baseline diagnosis of Alzheimer’s disease receiving vortioxetine in routine care settings (n = 207). Patients were assessed at baseline and after 8 weeks; a subset of patients was also assessed after 24 weeks. Depression severity was assessed using the Montgomery–Åsberg Depression Rating Scale (MADRS) and Clinical Global Impression (CGI) scale, cognitive symptoms using the Perceived Deficits Questionnaire–Depression, Korean version (PDQ-K), and cognitive performance using the Digit Symbol Substitution Test (DSST). Results Most patients were receiving a mean daily vortioxetine dose of 5 mg/day (174/190 patients; 91.6%). After 24 weeks of vortioxetine treatment, 71.4% of patients (40/56) had experienced overall clinical improvement (i.e., CGI–Improvement score ≤3) and 51.9% (28/54) had achieved remission from depressive symptoms (i.e., MADRS total score ≤10 points). Respective mean changes in MADRS, PDQ-K, and DSST total scores from baseline to week 24 were −11.5 (p < 0.0001), −5.1 (p = 0.03), and +3.8 points (p = 0.0524). Adverse events were reported by 27 patients (13.0%) and were mostly mild (89.2%). Conclusion Patients with MDD and comorbid Alzheimer’s disease receiving vortioxetine in routine care settings in South Korea demonstrated clinically meaningful improvements in depressive symptoms, cognitive symptoms, and objective cognitive performance over the 6-month treatment period. Treatment with vortioxetine was well tolerated in this patient cohort, with reported adverse events consistent with the established tolerability profile of vortioxetine.